(untitled) (Journal of Pathology of Nepal, 2015)
Background: Breast lump is a very common clinical presentation for which fine needle aspiration cytology is often sought for. Because of it’s significant diagnositic value, FNAC has become a routine tool in the evaluation of the nature of the lesion. The objective of this study was to determine the cytomorphological patterns of breast lump in eastern part of Nepal among individuals attending Nobel Medical College. Materials and Methods: This was a retrospective descriptive study done in department of pathology from December 2012 to June 2015. All individuals presenting with breast lumps was included in this study. FNAC was done as per standard procedure and categorized as per United Kingdom National Health Survey Breast Screening Programme (UK-NHS-BSP) categories and further also categorized in to neoplastic and non-neolastic categories. Results: We studied 771 cases of breast lumps. Occurrence of breast lump was more common in female (97.4%). Neoplastic lesions accounted for 84.1% of cases out of which benign comprised of 94.6% and malignant comprised of 5.6%. Common benign lesions observed were that of fibroadenona (264) and fibrocystic changes (204). Ductal carcinoma was the most common malignant lesions. All malignant lesions were observed in older age and female sex population. Conclusion: Most of the cases of breast lumps are benign in nature and very few accounted for malignant cases. There is predominance of benign lesions in young age and increased malignancy in older age and female population.